Why do patients with isolated PCL rupture experience no subjective knee joint instability during walking? An in vivo biomechanical study - Lu, Mingfeng; Chen, Wei; Lin, Jinpeng; Huang, Wenhan; Gao, Junqing; Zhao, Lilian; Li, Shilin; He, Lilei; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe aim of this study is to assess the kinematic changes in the knee joint during walking in patients with isolated PCL-deficiency (PCLD) to determine the presence of walking-related joint instability (mechanical instability—abnormal displacement form structural damage). Additionally, the study seeks to provide biomechanical insights into the observed differences between subjective and objective assessments.Methods35 healthy volunteers and 27 patients with isolated PCLD (both involved and uninvolved sides) were included in the study. All participants walked on a treadmill at a self-selected comfortable speed. An optical 3D motion capture system was employed to collect six degrees of freedom kinematic data of the knee joint during walking. Statistical Parametric Mapping (SPM) was employed, using independent and paired t-tests to evaluate differences between the healthy control group and the PCLD group, as well as between the involved and uninvolved sides, respectively.ResultsCompared with the healthy control group, posterior tibial displacement (the main indicator for anterior-posterior instability) of the involved limb was significantly decreased during 79%–94%. additionally, knee flexion angles of the involved limb were significantly increased compared with healthy control group during 0%–5% and 95%–99% of the gait cycle and significantly decreased during 66%–87%; In the uninvolved side, adaptive gait changes were observed, with knee flexion angles significantly reduced during 20%–50% and 64%–89% of the gait cycle and posterior tibial displacement significantly reduced during 60%–94% compared with the healthy control group; Compared to the uninvolved limb, the involved limb showed increased internal rotation during 62%–71% of the gait cycle and increased knee flexion during 8%–53%, with no significant differences in other dimensions.ConclusionFrom a biomechanical perspective, patients with PCL rupture exhibit no joint instability during walking. Compared to the healthy control group, the involved leg shows a significant reduction in posterior tibial displacement and a diminished range of knee flexion. Clinical evaluations of PCLD should incorporate dynamic functional assessments, thereby providing a more comprehensive basis for treatment decisions.